2022
DOI: 10.3390/geosciences12020055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Geological Heritage Sites and Their Significance for Geotouristic Exploitation: The Case of Lefkas, Meganisi, Kefalonia and Ithaki Islands, Ionian Sea, Greece

Abstract: Geological heritage or geoheritage refers to the total of geosites, i.e., areas of high geological interest in a given area. Geosites have a high potential of attracting geotourists, thus contributing to the development of the local economy. Assessing sites of geological interest can contribute to their promotion, as well as their preservation and protection. Greece’s geotectonic position in the convergent zone between the African and Eurasian plates has contributed to the existence of a considerable wealth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Messinian echinoderms from Kefalonia Island have also been reported by [30]. At the NW part of Mount Aenos, South Kefalonia, Upper Cretaceous limestones are mainly characterized by the abundance of rudists and rudist fragments [31]. In Livadi, West Kefalonia, similar rudist fragments were detected inside the local carbonate deposits [31].…”
Section: Fossils Of Kefalonia-ithaca Uggp-past Researchsupporting
confidence: 61%
See 1 more Smart Citation
“…Messinian echinoderms from Kefalonia Island have also been reported by [30]. At the NW part of Mount Aenos, South Kefalonia, Upper Cretaceous limestones are mainly characterized by the abundance of rudists and rudist fragments [31]. In Livadi, West Kefalonia, similar rudist fragments were detected inside the local carbonate deposits [31].…”
Section: Fossils Of Kefalonia-ithaca Uggp-past Researchsupporting
confidence: 61%
“…At the NW part of Mount Aenos, South Kefalonia, Upper Cretaceous limestones are mainly characterized by the abundance of rudists and rudist fragments [31]. In Livadi, West Kefalonia, similar rudist fragments were detected inside the local carbonate deposits [31]. Pliocene sediments rich in Pectinidae, Ostreidae, and Echinidae have been found in the geosites of Ai Helis and Agios Thomas [12].…”
Section: Fossils Of Kefalonia-ithaca Uggp-past Researchmentioning
confidence: 99%
“…Various approaches are used for the purposes of effective geoheritage management. These were reviewed by Bratton et al [67], Cayla [68], de Oliveira et al [69], Erikstad [70], Fuertes-Gutiérrez et al [71], Lech et al [72], Lima et al [73], Mucivuna et al [74], Pál and Albert [75], Prosser et al [76], Reynard and Brilha [77], and Spyrou et al [78]. In regard to the state of three considered geoheritage points (see above) and the entire geoheritage of Mountainous Adygeya [26], five managerial actions can be recommended.…”
Section: Geoheritage Management Implicationsmentioning
confidence: 99%
“…With the values of geoethics, the integration between geodiversity and cultural resources is able to develop the needed sense of responsibility for preserving geoheritage, not only for the enjoyability of the present communities but also for assuring its existence for the future generations [15,22]. Greece denotes an exceptional example of a geotope ensemble with solid geotouristic potential [2,7,8,[23][24][25][26]. In particular [6,7], after evaluating more than 500 geotopes of the Hellenic territory, concluded that Greece holds high geotouristic perspectives that can further support the vital tourism sector and the regional development of the Greek economy via the management of the geotopes as attractive local tourism products.…”
Section: Introductionmentioning
confidence: 99%